Economic growth of agglomerations and geographic concentration of industries: Evidence for Germany - Kurt Geppert; Martin Gornig; Axel Werwatz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The vast majority of regions in West Germany, and the EU, have become more similar in terms of per-capita income and productivity between 1980 and 2000. But a number of rich areas - generally large agglomerations - have succeeded in departing from this trend of convergence. They are continuing to rise above the average productivity level. We examine whether this development can also be seen as due to changes in the spatial distribution of economic sectors. Knowledge-intensive services in particular are identified as industries that combine employment growth and further geographical concentration. Logistical and nonparametric regressions confirm a positive relation between the regional weight of sectors that are continuing to concentrate geographically and the probability that this region will develop ahead of the general trend. We find that increasing localisation of fast growing industries is an important factor behind the changes in the spatial pattern of the economy.
Keywords: C14; C16; R12; R30; 330; regional convergence; knowledge-intensive services; industry-specific local linkages; logistical regressions; non-parametric regressions